OCTOVA: A randomised phase II trial of olaparib, chemotherapy, or olaparib and cediranib in patients with BRCA-mutated platinumresistant ovarian cancer - Nicum, S; Strauss, V; McGregor, N; McNeish, I; Roux, R; Hall, M; Michael, A; Roberts, C (Oxford University Press, 2017)
Women with platinum resistant ovarian cancer (OC) have limited responses to standard therapy, and clinical trials with novel agents are therefore highly justified. Olaparib is a potent PARP inhibitor that has shown enhanced activity in women with relapsed BRCA-mutated OC in both platinum sensitive and resistant settings. Angiogenesis inhibitors, such as the oral tyrosine kinase inhibitor cediranib, are active in OC, and have shown additive effects when combined with PARP inhibitors preclinically, as hypoxia-induced downregulation of homologous recombination repair genes, BRCA1, 2 and RAD51 enhances PARP inhibitor sensitivity. Recent phase 2 trials in relapsed platinum-sensitive OC have also shown benefit from the combination of olaparib and cediranib compared to olaparib alone. The OCTOVA trial investigates the benefit of single agent olaparib compared to olaparib and cediranib or weekly paclitaxel in women with BRCA-mutated platinum-resistant OC.